Quality improvement priorities for safer out-of-hours palliative care: Lessons from a mixed-methods analysis of a national incident-reporting database. (March 2019) - Williams, Huw; Donaldson, Sir Liam; Noble, Simon; Hibbert, Peter; Watson, Rhiannon; Kenkre, Joyce; Edwards, Adrian; Carson-Stevens, Andrew
Background: Patients receiving palliative care are often at increased risk of unsafe care with the out-of-hours setting presenting particular challenges. The identification of improved ways of delivering palliative care outside working hours is a priority area for policymakers. Aim: To explore the nature and causes of unsafe care delivered to patients receiving palliative care from primary-care services outside normal working hours. Design: A mixed-methods cross-sectional analysis of patient safety incident reports from the National Reporting and Learning System. We characterised reports, identified by keyword searches, using codes to describe what happened, underlying causes, harm outcome, and severity. Exploratory descriptive and thematic analyses identified factors underpinning unsafe care. Setting/participants: A total of 1072 patient safety incident reports involving patients receiving sub-optimal palliative care via the out-of-hours primary-care services. Results: Incidents included issues with: medications (n = 613); access to timely care (n = 123); information transfer (n = 102), and/or non-medication-related treatment such as pressure ulcer relief or catheter care (n = 102). Almost two-thirds of reports (n = 695) described harm with outcomes such as increased pain, emotional, and psychological distress featuring highly. Commonly identified contributory factors to these incidents were a failure to follow protocol (n = 282), lack of skills/confidence of staff (n = 156), and patients requiring medication delivered via a syringe driver (n = 80). Conclusion: Healthcare systems with primary-care-led models of delivery must examine their practices to determine the prevalence of such safety issues (communication between providers; knowledge of commonly used, and access to, medications and equipment) and utilise improvement methods to achieve improvements in care.